Руководство для уставших : как понимать себя и других - Stafford, Rachel Macy, 1972- (New psychology, 2025)
"An experiential guide to help bring you back to what delights your heart and brings you peace ... Filled with fun, easy-to-follow exercises, Soul Shift helps you overcome barriers that prevent you from being present in your own life. With eight illuminating territories to explore, you'll learn how to move away from self-sabotaging habits by practicing presence, worthiness, self-kindness, authenticity, forgiveness, looking after yourself, letting go of perfectionism, and utilizing your gifts"